Grigoriy Vasilievich Bondar (Experimental Oncology, 2014)
Ukrainian oncology has suffered an irretrievable loss. Outstanding Ukrainian oncologist and surgeon, Hero of Ukraine, Honored Science and Technology Worker of Ukraine, general director of Donetsk Regional Anticancer Center, Head of the Chair of Oncology of Maxim Gorky Donetsk National Medical University, member of National Academy of Medical Sciences of Ukraine — Grigoriy Vasilievich Bondar died at the age of 81.